Effects of balancing hamstring and quadriceps muscle torque on running technique - Rosemond, D.; Blanch, P.; Smith, R.; Bidder, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The increased effectiveness of running technique was associated with foot activity prior to and during initial foot contact where hamstring EMG activity was at its highest. Changes to running technique are likely to be the result of factors related to improved hamstring strength. As post intervention values for Hecc/Qconc ratios were below the critical value (0.87) (Croisier et al 2008), further improvements in running technique variables could be expected with future strength gains. The athlete has since incurred a hamstring strain providing an opportunity to investigate the outcomes of his recovery in relation to running technique and leg strength.